State, crisis and politicisation of economic policymaking: reflections from Hungary and Turkey - Center for Policy Studies, Budapest; Donmez, Pinar; Zemandl, Eva (Budapest, 2015)
"This working paper aims to explore the increasing role and impact of government-led repoliticization in Hungary and Turkey in the context of the post-2008 crisis and restructuring. Politically and economically positioned within the periphery of Europe both countries have gone through a thorough restructuring process in the pre-2008 context. Whilst this process has introduced and consolidated depoliticized forms of governance to a certain degree in both countries, the global crisis from 2008 onwards is claimed to have led to the emergence of a reverse process of politicisation towards a clearly visible ministerial control over the management of money in the Hungarian context and the intensifying discursive attempts to politicize monetary policymaking in the Turkish context while still retaining its formally depoliticized character in material terms. Similarly in both countries the process has been going hand in hand with the entrenchment of an increasingly authoritarian discourse and practices in various issue and policy areas as part of the overall management of the crisis-ridden capitalist social relations. The paper aims to explore these similarities and differences in these country contexts within a critical framework of (de)politicization and make an original contribution in advancing research in this field beyond the established case studies in the existent literature by focusing on the periphery of Europe."